Letter to the Editor about the Article: “Still Regarding Anxiety, Depression and Academic Performance: A Study Amongst Portuguese Medical Students Versus Non-Medical Students”, by João Moreira de Sousa, Cátia A. Moreira, Diogo Telles-Correia. Acta Med Port. 2018;31:454-62. - Gama Marques, João (2018)
N/A.